Omeprazole: Inhibiting the Final Common Pathway to Acid Secretion - The Acid Pump - A.B.R. Thomson (Canadian Journal of Gastroenterology)
Omeprazole is the first agent in a new therapeutic advance class the proton or acid pump inhibitors which represents a significant therapeutic advance in the treatment of acid related diseases. Omeprazole reduces gastric acid secretion at its source – the acid pump of the parietal cell, thereby offering precise and consistent clinical effects. Omeprazole once daily has been shown to heal over 80% of duodenal ulcers within two weeks and over 95% within four weeks In gastric ulcer, the healing rates are up to 80% within four weeks and 96% within eight weeks. More patients are free from symptoms earlier on omeprazole therapy than with the H2 receptor antagonists. Omeprazole is also effective in healing and symptom relief even where prolonged H2 receptor antagonist therapy has been unsuccessful. Omeprnzole has been shown in clinical trials to be the first consistently effective treatment of erosive/ulcerative reflux esophagitis. Complete healing is achieved in the majority of patients and symptom relief is rapid. In clinical trials with 20 mg once daily, over 70% of patients healed within four weeks and up to 85% healed within eight weeks. Also. patients with erosive/ulcerative reflux esophagitis resistant to three months or more of treatment with full therapeutic doses of H2 receptor antagonists have shown significant benefit, with healing rates of 49% within four weeks and 73% within eight weeks of therapy with omcprazole. The rare Zollinger-Ellison syndrome has been difficult to treat in the past due to the massive hypersecretion of gastric acid Omeprazole has proved highly effective in this syndrome, being well tolerated by patients who have received more than five years of continuous treatment with daily oral doses up to 160 mg. In summary, in extensive clinical trials omeprazole has been shown to be highly effective in the treatment of duodenal and gastric ulcers, erosive/ulcerative reflux esophagitis and Zollinger-Ellison syndrome. Omeprazole is well tolerated and is without any established side effects when used for short periods. It remains to be established whether H2 blockers still represent the best available therapy for acute treatment of peptic disorders, and whether maintenance therapy is best achieved with H2 blockers or with proton pump blockers.